A STRATEGY FOR SUSTAINABLE WASTE MANAGEMENT IN OIL AND GAS INDUSTRY - Dwi Anggoro Ismukurnianto (Scientific Contributions Oil and Gas, 2003)
Oil and gas industries unavoidably generate huge quantity of waste during their activities including exploration, production, storage, gathering, processing, transmission, distribution or combination of these.